Response to “the Future of Pain Medicine: Emerging Technologies, Treatments, and Education” [Letter] - Guan Y; Zhang J; Cai L (Journal of Pain Research)
Yubo Guan, Jiannan Zhang, Liangyu Cai Wuxi Affiliated Hospital of Nanjing University of Chinese Medicine, Wuxi, People’s Republic of ChinaCorrespondence: Liangyu Cai, Wuxi Affiliated Hospital of Nanjing University of Chinese Medicine, No. 8, Zhongnan West Road, Binhu District, Wuxi City, Jiangsu Province, People’s Republic of China, Email wxzy018@njucm.edu.cn